2023
DOI: 10.21203/rs.3.rs-2664326/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antioxidant activity of flavonoids and phenolic acids from Dodonaea angustifolia flower: HPLC profile and PASS prediction

Abstract: Background Dodonaea angustifolia is a known medicinal plant across East Arica. The flower of D. angustifolia is not well investigated in terms of phytochemistry and biological activities. This study aims to investigate the presence of flavonoids and phenolic acid in the flower of D. angustifolia and its antioxidant activity. Methods Preliminary phytochemical screening was carried out using standard protocols. Antioxidant activity evaluation using DPPH assay and total phenol content (TPC) and total flavonoid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…In our previous study, using HPLC analysis, we identified and quantified the three phenolic acids, including chlorogenic acid, gallic acid, and syringic acid, in methanol extract of D. angustifolia flower extract, which is in close agreement with the current HPTLC analysis result [ 34 ]. Similar to the HPLC data presented in our earlier work, the HPTLC profiles ( Figure 2 and Figure 3 ) and peak tables ( supplementary file, Tables S1 and S2 ) provide information regarding the presence of flavonoids and phenolic acids.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In our previous study, using HPLC analysis, we identified and quantified the three phenolic acids, including chlorogenic acid, gallic acid, and syringic acid, in methanol extract of D. angustifolia flower extract, which is in close agreement with the current HPTLC analysis result [ 34 ]. Similar to the HPLC data presented in our earlier work, the HPTLC profiles ( Figure 2 and Figure 3 ) and peak tables ( supplementary file, Tables S1 and S2 ) provide information regarding the presence of flavonoids and phenolic acids.…”
Section: Discussionsupporting
confidence: 80%
“…From a prior investigation on the flower of D. angustifolia [ 34 ], it was revealed that almost similar phytochemical screening results show both the leaf and flower are rich in phenolic acids and flavonoids. Furthermore, we have compared both samples’ antioxidant activity and total phenolic and flavonoid contents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations